TARAS SHEVCHENKO IN THE CONTEXT OF MUSICAL CULTURE OF POSTMODERNISM (AS AN INSTANCE OF ORATORIO NEOPHITES OF MARIIAN KUZAN) - Karas, H. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Creative works of Ukrainian poet T. Shevchenko in a context of musical culture of postmodernism based on an example of oratorio Neophites of a French-Ukrainian composer Mariian Kuzan are researched in the article. The research utilizes integral interdisciplinary approaches: philosophical study of Shevchenko, philosophy of music, semiotics aspects and idea of ethnocentrism.